Development of Realistic Mathematics Education (RME) Integrating Agricultural Activities to Improve Numeracy Skills - Cahyadewi, Karina Cindy; Pambudi, Didik Sugeng; Lestari, Nurcholif Diah Sri; Kurniati, Dian; Kristiana, Arika Indah (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to develop Realistic Mathematics Education (RME) learning tools integrated with agricultural activities, fulfilling the criteria of valid, practical, and effective to improve numeracy skills, particularly in the topics of direct and inverse proportionality. This study used the research and development with the Plomp model, comprising three phases. The first phase, preliminary research, involved 26 teachers and prospective teachers. The second phase, development or prototyping, engaged three experts and three students. The third phase, assessment, was conducted through trial testing with 31 participants in the experimental class and 31 participants in the control class. Data collection techniques included questionnaires, surveys, observations, tests, and interviews. Data processing was conducted using descriptive statistics. The results of the study indicate that the developed RME learning tools integrated with agricultural activities fulfills the criteria of valid, practical, and effective. The validity criteria were achieved with scores of 3.77 for the teaching module, 3.81 for the LKPD, 3.84 for the learning achievement test, and 3.87 for the instruction manual. The practicality criteria were met with a learning implementation rate of 95% (very good), and student activity reaching 84.9% (active). Additionally, student and teacher response questionnaires showed positive feedback, with scores of 95.48% and 100%, respectively. The effectiveness criteria were achieved with an average N-Gain score of 0.65 (moderate) and the experimental class achieved higher average scores than the control class. This study implies that RME integrated with agricultural activities can be recommended for mathematics teachers to support numeracy teaching.